Global, regional, and national burden of inflammatory bowel disease in persons aged 60–89 years from 1992 to 2021 - Zhou Zhang; Na Du; Chun-mei Xu; Wei Chen; Ting-ting-Chen; Yu Xiao (BMC Gastroenterology)
Abstract Background The global burden of inflammatory bowel disease (IBD) is increasing, but detailed data on older adults remain scarce. Objective This study describes trends in incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of IBD among individuals aged 60–89 years from 1992 to 2021 at global, regional, and national levels, and forecasts the epidemiological status for 2030. Methods We used the Global Burden of Disease (GBD) database, covering 204 countries and territories. Temporal trends were analyzed using Joinpoint regression models. Decomposition analysis assessed the impacts of population growth, aging, and epidemiological changes. The Nordpred model forecasted 2030 incidence, prevalence, mortality, and DALYs of IBD among older adults. Results From 1992 to 2021, the global age-standardized incidence rate (ASIR) of IBD among older adults increased (AAPC 0.34). Conversely, the prevalence rate (ASPR) slightly decreased (AAPC − 0.04). Both mortality (ASMR) and DALYs significantly declined (AAPC − 0.60 and − 0.49, respectively). High SDI regions had the highest ASIR and ASPR, with Middle SDI regions experiencing the fastest ASIR growth. Population growth accounted for 117.77% of the overall increase in the IBD burden. By 2030, the incidence rate is expected to rise, but prevalence, mortality, and DALYs rates are predicted to decrease. Conclusion The incidence rate of IBD among older adults is rising, while prevalence, mortality, and DALYs rates are declining. Significant regional variations underscore the need for targeted public health policies.